Adjunctive use of essential oils following scaling and root planing –a randomized clinical trial. Issue 1 (December 2016) - Azad, Mohammad; Schwiertz, Andreas; Jentsch, Holger
Abstract Background Hitherto no study has been published on the effect of the adjunctive administration of essential oils following scaling and root planing (SRP). This study describes the effect of a mouthrinse consisting of essential oils (Cymbopogon flexuosus, Thymus zygis andRosmarinus officinalis ) following SRP by clinical and microbiological variables in patients with generalized moderate chronic periodontitis. Methods Forty-six patients (aged 40–65 years) with moderate chronic periodontitis were randomized in a double-blind study and rinsed their oral cavity following SRP with an essential oil mouthrinse (n   =  23) or placebo (n   =  23) for 14 days. Probing depth (PD), attachment level (AL), bleeding on probing (BOP) and modified sulcus bleeding index (SBI) were recorded at baseline and after 3 and 6 months. Subgingival plaque was taken for assessment of major bacteria associated with periodontitis. Results AL, PD, BOP and SBI were significantly improved in both groups after three (p    <   0.001) and 6 months (p    ≤   0.015). AL improved significantly better in the test than in the control group after 3 and 6 months (p  < 0.001), so did PD after three months in the tendency (p   =  0.1). BOP improved better in the test group after 3 months (p   =  0.065). Numbers ofTreponema denticola (p   =  0.044) andFusobacterium nucleatum (p   =  0.029) decreased more in the test than in the control group after 3 months, those ofTannerella forsythia after 6 months (p   =  0.039).Prevotella micra (p  <  0.001,  p   =  0.035) andCampylobacter rectus (p   =  0.002 ,  p   =  0.012) decreased significantly in both groups after 3 months. Conclusions The adjunctive use of a mouthrinse containing essential oils following SRP has a positive effect on clinical variables and on bacterial levels in the subgingival biofilm. Trial registration 332-12-24092012, DRKS 00009387, German Clinical Trials Register, Freiburg i. Br., 16.09.2015